Treatment Outcomes of Tuberculosis at Asella Teaching Hospital, Ethiopia: Ten Years’ Retrospective Aggregated Data - Tafess, Ketema; Beyen, Teresa Kisi; Abera, Adugna; Tasew, Geremew; Mekit, Shimelis; Sisay, Solomon; Tadesse, Legesse; Siu, Gilman K. H. (Frontiers in Medicine, 2018)
Background: Directly Observed Treatment Short-course (DOTS) has been one of the major strategies to combat the epidemic of tuberculosis (TB) globally. This study aimed to evaluate TB treatment outcomes between September 2004 and July 2014 under the DOTS program at one of the largest public hospitals in Ethiopia. Methods: A retrospective data of TB patients registered at Asella Teaching Hospital between September 2004 and July 2014 were obtained from hospital registry. Treatment outcomes and types of TB cases were categorized according to the national TB control program guideline. Binomial and multinomial logistic regression models were used to analyze the association between treatment outcomes and potential predictor variables. Results: A total of 1,755 TB patients’ records were included in the study. Of these, 945 (53.8%) were male, 480 (27.4%) smear positive TB, 287 (16.4%) HIV positive, and 1,549 (88.3%) new cases. Among 480 smear positive pulmonary TB cases, 377 (78.5%) patients were cured, 21 (4.40) completed the treatment, 35 (7.3%) transferred out, 19 (4.0%) died, 24 (5.0%) defaulted, and 4 (0.8%) failure. Overall, 398 (82.9%) smear positive pulmonary TB patients were successfully treated. For smear negative TB (n=641) and extra-pulmonary TB cases (n=634), 1036 (81.3%) completed the treatment and demonstrated favorable response. Taking all TB types into account, 1434 (81.7%) were considered as successfully treated. In the multivariate binary logistic model, patients in older age group (AOR = 0.386, 95% CI: 0.250-0.596) and retreatment cases (AOR = 0.422, 95% CI: 0.226-0.790) were less likely to be successfully treated compared to younger and new cases, respectively. In multinomial logistic regression, age increment by 1 year increased the risk of death and default of TB patients by 0.05 (adjusted β=0.05; 95% CI: 0.03, 0.06) and 0.02 (adjusted β= 0.02; 95% CI: 0.01, 0.04). The odds of TB patients who died during treatment were higher among HIV-infected TB patients (adjusted β = 2.65; 95% CI: 1.28, 5.50). Conclusions: The treatment success rate of TB patients was low as compared to the national target. TB control needs to be strengthened for the enhancement of treatment outcome. Keywords: Tuberculosis, Asella, outcomes, Smear positive pulmonary tuberculosis, Smear-negative